A subjetividade neoliberal: implicações do discurso do capitalista entre os motoristas do aplicativo Uber em Fortaleza - CE - Araújo, Neiara Parente de (2022)
The political-economic transformations, in contemporary capitalist civilization, given in the neoliberal perspective, demand analysis, since they are new expressions of capital. In this so- cialization, the use of the Lacanian device “discourse of the capitalist” has been intensifying. It is established to provide the entrepreneurial subject, like the application workers. These workers hold a portion of the means of production and their workforce, however, within the scope of new forms of capital dominance, they are considered entrepreneurs as if they were owners of production and determined their labor activity. Such influence concerns the formu- lated neoliberal subjectivation, through knowledge of book value that pronounces a certain truth and produces a drive-like purpose. Neoliberal subjectivity, being defined by the accoun- ting knowledge of the capitalist discourse, endlessly seeks income. He understands that finan- cial gains will give him psychic enjoyment. However, does it present a certain impasse or is it in fact in the effects of the capitalist discourse? Does it have flaws or does it intensify the sub- ject's alienation? Is it possible, with the discourse of the capitalist, to reach jouissance? Fi - nally, to what extent does the capitalist discourse influence the subjectivity of men and wo- men Uber partner drivers? It is believed that it is not possible to apprehend jouissance, as it is primarily constituted under the register of the real, which cannot be symbolized. Even so, the capitalist's discourse tries to undo the symbolic order of language, developed in culture, in or- der to achieve psychic enjoyment. Due to the problematization, the present dissertation aimed to verify the psychic effects of neoliberalism. For this, he investigated the concepts of capita- list discourse and neoliberalism, obtained information about working with Uber on the com- pany's website, applied questionnaires to Uber drivers, conducted interviews with Uber appli- cation workers and analyzed the expressed speeches. The qualitative research used three me- thods: bibliographic survey, questionnaires and interviews. The results showed heterogeneous perceptions of drivers about their relationship with Uber. Some see themselves as entrepre- neurs, others see themselves as employees of the platform. It was possible to perceive effects of the capitalist's discourse, but it was not completely equal among the drivers. There are still, in uberization, problems to be investigated. More research is needed on the subordinate self- management present in uberization, a concept that brings the ambiguity of the phenomenon.